Anaplasma phagocytophilum and Babesia spp. in roe deer (Capreolus capreolus), fallow deer (Dama dama) and mouflon (Ovis musimon) in Germany. (February 2017) - Kauffmann, Melanie; Rehbein, Steffen; Hamel, Dietmar; Lutz, Walburga; Heddergott, Mike; Pfister, Kurt; Silaghi, Cornelia
Abstract: Infections with the tick-borne pathogens Anaplasma phagocytophilum and Babesia spp. can cause febrile disease in several mammalian species, including humans. Wild ruminants in Europe are suggested to serve as reservoir hosts for particular strains or species of these pathogens. The aims of this study were to investigate the occurrence of A. phagocytophilum and Babesia spp. in roe deer ( Capreolus capreolus ), fallow deer ( Dama dama ) and mouflon ( Ovis musimon orientalis ) in Germany, and the diversity and host association of genetic variants of A. phagocytophilum and Babesia species. From 2009 to 2010, 364 spleen samples from 153 roe deer, 43 fallow deer and 168 mouflon from 13 locations in Germany were tested for DNA of A. phagocytophilum and Babesia spp. by real-time PCR or conventional PCR, respectively. Variants of A. phagocytophilum were investigated with a nested PCR targeting the partial 16S rRNA gene, and species of piroplasms were identified by sequencing. DNA of A. phagocytophilum was detected in 303 (83.2%) samples: roe deer, 96.1% (147/153); fallow deer, 72.1% (31/43); and mouflon, 74.4% (125/168). Sequence analysis of 16S rRNA -PCR products revealed the presence of nine different genetic variants. DNA of Babesia spp. was found in 113 (31.0%) samples: roe deer, 62.8% (96/153); fallow deer, 16.3% (6/43); and mouflon, 6.5% (11/168). Babesia capreoli, Babesia sp. EU1 (referred to also as B. venatorum ), B. odocoilei -like and a Theileria species were identified. Co-infections with A. phagocytophilum and Babesia spp. were detected in 30.0% of the animals which were tested positive for A. phagocytophilum and/or Babesia spp. Roe deer had a significantly higher percentage of co-infections (60.8%), followed by fallow deer (14.0%) and mouflon (6.5%). Thus, the results suggest that roe deer plays a key role in the endemic cycles of the pathogens investigated. Highlights: A. phagocytophilum and Babesia spp. was investigated in roe deer, fallow deer and mouflon with special attention to sympatric populations. A. phagocytophilum and Babesia were detected in all species examined, partially with high infection rates. DNA of A. phagocytophilum was found in 303 (83.2%) samples and Babesia spp. was found in 113 (31.0%) samples. First report of B. capreoli and B. venatorum DNA in mouflon in Europe and any Babesia DNA in fallow deer in Germany. Results suggest that roe deer plays key role in endemic cycles of the pathogens investigated.